Manufacturing hybrid busbars through joining by forming - Pragana, João (2021)
This paper focus on the production of hybrid busbars made from copper and aluminium by means of a joining by forming process that was recently developed by the authors. The process involves the combined use of partial cutting and bending with form-fit joining by compression in the direction perpendicular to strip thickness. The resulting joints are flat with the plastic deformed materials enclosed within the thickness of the overlapped strips. Design is performed by means of an analytical model and the overall manufacturing concept is validated through numerical and experimental modelling. Major process parameters are identified and their influence on the overall deformation mechanics and joining feasibility is investigated. The effectiveness and performance of the new joints is analysed by means of tensile-shear loading tests. Results show that joining by forming can be successfully utilized to produce form-fit joints with good shear forces in hybrid busbars for electrical applications.